Changes in pH Increase Perfusion Pressure of Coronary Arteries in the Rat - Yasushi Horai; Ken-Ichi Furukawa; Shingo Iwata; Yasushi Ohizumi (Elsevier, 2005)
Stricture of coronary arteries is closely related to ischemic heart disease. The purpose of this study was to examine whether changes in pH caused contraction of rat coronary arteries, as determined using Langendorff perfused hearts. Changing the pH of the perfusate increased perfusion pressure as an indication of the contractile state of coronary arteries. Alkaline pH-induced increase of perfusion pressure in Wistar Kyoto rats (WKY) was almost identical to that of spontaneously hypertensive rats (SHR), whereas acidic pH-induced increase in SHR was much greater than that in WKY. Acidic pH-induced increase in perfusion pressure was inhibited by verapamil, cromakalim, and adenosine. Feeding WKY with NG-nitro-L-arginine resulted in hypertension followed by enhanced acidic pH-induced increase in perfusion pressure. These results suggest that acidic-pH induced contraction of rat coronary arteries is caused by Ca2+ influx through voltage-dependent Ca2+ channels and the contraction is enhanced by hypertension. Keywords:: acidosis, coronary perfusion pressure, hypertension, vascular smooth muscle, spontaneously hypertensive rat